Big and "unprofitable": How 10% of multinational firms do 98% of profit shifting - Ludvig Wier; Hayley Reynolds (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Globally, the largest 0.001 per cent of firms earn roughly one-third of all corporate profits. Nonetheless, there is little understanding of how profit shifting differs across firm size. Using South African corporate tax returns from 2010-14, we investigate the link between firm size and profit shifting. We estimate that firms owned by a parent in a tax haven avoid taxation on as much as 80 per cent of their true income. However, this aggregate tax loss conceals large differences across firms. The majority of firms shift little income to tax havens, while a few large firms shift a lot. The top decile of foreign-owned firms accounts for 98 per cent of the total estimated tax loss. This extreme concentration of tax planning has not been documented before and has implications for both research and policy. First, our results imply that tax havens create competitive distortions as larger firms benefit more. Second, as past research does not account for heterogeneity across firms, it may underestimate the total tax loss caused by profit shifting. As an illustration of this, we revisit the OECD's official estimate of profit shifting and find that profit shifting may have been dramatically underestimated.
Keywords: H25; H26; H87; O23; 330; tax; international taxation; profit shifting; multinational firms; developing countries